Potential of Dietary Flavonoids in The Prevention and Therapy of COVID-19 : Focusing in Mast Cell - Calcium Ion Channel Axis - Tedjo, Aryo (UI Scholars Hub, 2023)
Syndrome Acute Respiratory Syndrome Corona Virus-2 (SARS COV2) is the virus that causes the COVID19 disease and has caused more than 4 million deaths worldwide. This virus infects the host cell through the interaction between the virus’s glycoprotein S molecule with the ACE2 which is the virus receptor, binding, undergoes membrane fusion and enters the cell and replicates in it. Currently, several strategies used in developing anti-viral compounds are targeting compounds that play a role in the process of entering the virus into host cells such as ACE2, S glycoprotein, and TMPRSS2, while some target main proteases such as RNA dependent Polymerase and N proteins. On the other hand, one of the causes for the worsening of COVID-19 cases is hyperinflammation. This condition can also be caused by an increase in calcium consumption activity which is responsible for the process of viral endocytosis, mast cell recruitment, and also the recruitment of surrounding cells to form syncytia. Under these conditions, virions that are trapped and accumulated in the syncytia can initiate the release of virions and pro-inflammatory molecules, leading to hyperinflammation and second week crash. This review will explain the importance of the role of calcium ions and mast cells in mediating inflammation as well as the prospect of inhibiting hyperinflammation in COVID19 using flavonoid compounds contained in daily food ingredients.